Directions: Use laws of exponents to simply the following. (Show your solution)
![Directions Use Laws Of Exponents To Simply The Following Show Your Solution class=](https://ph-static.z-dn.net/files/dff/742fed49e523df4589e31aa2bd5fb37a.png)
1] (a – 2) – (a – 9)
= a – 2 – a + 9
= – 2 + 9
= 7
2] (b⁵ – b³) – (b⁴ – b²)
= b⁵ – b⁴ – b³ + b²
3] (a² – 6ab + 7) –5a² – 5ab – 2
= a² – 5a² – 6ab – 5ab + 7 – 2
= –4a² – 11ab + 5
4] (–3x³ + 8x² – 10) – (2x³ – 5x – 3)
= –3x³ – 2x³ + 8x² + 5x – 10 + 3
= –5x³ + 8x² + 5x – 7
5] (5 – 6x + 2x³) – (2x³ – 4x + 3)
= 5 – 6x + 2x³ – 2x³ + 4x – 3
= –6x + 4x + 5 – 3
= –2x + 2